(untitled) (Research, Society and Development, 2025)
Ora-pro-nóbis (Pereskia aculeata Miller) is a medicinal plant with high nutritional potential and significant relevance for scientific research due to its rich composition. This study aimed to obtain and characterize the flour made from ora-pro-nóbis leaves. For this purpose, the leaves were subjected to blanching, drying, and grinding. The resulting flour was then characterized in terms of oxalic acid content, protein content, and microbiological quality. To evaluate the bioactive compounds, extracts of the flour and their fractions were analyzed using Thin Layer Chromatography (TLC), followed by the quantification of phenolic compounds. Additionally, the effect of the ora-pro-nóbis extract on the activity of the enzyme acetylcholinesterase (AChE) in lymphocytes and the antimicrobial activity of the extracts were evaluated. The results showed that the blanching process reduced the oxalic acid content by 39%. A high protein content was confirmed in the flour (approximately 20.04%), along with the presence of terpenes, flavonoids, alkaloids, and unsaturated substances. The ethyl acetate extract contained 115.02 mg of phenolic compounds per gram of extract; however, no significant changes were observed in AChE activity in lymphocytes. On the other hand, this extract demonstrated antimicrobial activity against Escherichia coli. Moreover, the flour was considered safe for consumption. It is concluded that ora-pro-nóbis flour represents a viable dietary alternative due to its multiple nutritional and bioactive benefits.